PENGEMBANGAN MEDIA POHON PINTAR MATERI SUKU KATA PADA MATA PELAJARAN BAHASA INDONESIA KELAS I - Afdana Afdana; Kartini Kartini; A. Wilda Indra Nanna (Universitas Borneo Tarakan, 2025)
This study aimed to develop a smart tree learning media for the Indonesian Language subject on syllable material for Gtade I-A at SDN 013 Tarakan. Bassed on initial observations, issues were identified in students understanding of syllable reading.This was attributed to the lack of engaging media used by teachers during the learning process. This study employed the research and development (R and D) method using the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. The research results indicated that the developed Smart Tree media is feasible based on validation from media experst and subject matter experts. The validation results obtained from media experts achieved a percentage of 90%, and subject matter experts achieved a percentage of 80%. Additionally, the limited trial achieved a percentage of 96%, and the field trial achieved a percentage of 99%. The teacher response questionnaire results obtained a percentage of 100%. The validation results from media experts and subject matter experts indicated that the Smart Tree media is highly feasible for use in the learning process. The teacher and student response questionnaire results duringthelimitedtrialandfieldtrialindicatethatstudents’interestinthe Smart Tree media is very high.